Exploring Non-Expert Robot Programming Through Crowdsourcing - van Waveren, Sanne; Carter, Elizabeth J.; Örnberg, Oscar; Leite, Iolanda (Frontiers in Robotics and AI, 2021)
A longstanding barrier to deploying robots in the real world is the ongoing need to author robot behavior. Remote data collection -particularly crowdsourcing- is increasingly receiving interest. In this paper, we make the argument to scale robot programming to the crowd and present an initial investigation of the feasibility of this proposed method. Using an off-the-shelf visual programming interface, non-experts created simple robot programs for two typical robot tasks (navigation and pick-and-place). Each needed four subtasks with an increasing number of programming statements (if statement, while loop, variables) for successful completion of the programs. Initial findings of an online study (N = 279) indicate that non-experts, after minimal instruction, were able to create simple programs using an off-the-shelf visual programming interface. We discuss our findings and identify future avenues for this line of research.